Armillaria mellea Symbiosis Drives Metabolomic and Transcriptomic Changes in Polyporus umbellatus Sclerotia - Xing, Yong-Mei; Li, Bing; Liu, Liu; Li, Yang; Yin, Shu-Xue; Yin, Shu-Chao; Chen, Juan; Guo, Shun-Xing (Frontiers in Microbiology, 2022)
Sclerotia, the medicinal part of Polyporus umbellatus, play important roles of diuresis and renal protection, with steroids and polysaccharides as the main active ingredients. The sclerotia grow and develop only after symbiosis with Armillaria sp. In this study, a systematic metabonomics study based on nontargeted UPLC-MS method was carried out between the infected part of the separated cavity wall of the sclerotia (QR) and the uninfected part (the control group) to find and identify differential metabolites. The biosynthetic pathway of characteristic steroids in sclerotia of P. umbellatus was deduced and the content of ergosterol, polyporusterone A and B in the QR and CK groups were detected with the High Performance Liquid Chromatography (HPLC). Furthermore, the expression patterns of putative genes associated with steroid biosynthesis pathway were also performed with quantitative real-time PCR. The results showed that a total of 258 metabolites originated from fungi with the fragmentation score more than 45 and high resolution mass were identified, based on UPLC-MS metabonomics analysis, and there were 118 differentially expressed metabolites (DEMs) between the both groups. The metabolic pathways indicated that steroids, fatty acid and carbohydrate were active and enriched during P. umbellatus sclerotia infected by A. mellea. The content of ergosterol, polyporusterone A and B in the QR group increased by 32.2%, 75.0% and 20.0%, in comparison to that of the control group. The qRT-PCR analysis showed that series of enzymes including C-8 sterol isomerase (ERG2), sterol C-24 methyltransferase (ERG6) and sterol 22-desaturase (ERG5), which played important roles in the final steps of ergosterol biosynthesis, all presented up-regulated patterns in the QR group in P. umbellatus. The comprehensive metabolomic and transcriptomic information will contribute to further study concerning the mechanisms of P. umbellatus sclerotial formation infected by A. mellea in the future.